Taxonomic revision of two poorly known genera of Richardiidae (Diptera): Maerorichardia and Odontomerella - Lisiane Dilli Wendt; Luciane Marinoni (Zoologia (Curitiba), 2015)
ABSTRACT Richardiidae are a family of Tephritoidea in which most genera are poorly known taxonomically, including some which were poorly described with limited or no illustrations. With the aim to decrease this taxonomic gap, herein we review two scarcely known monotypic genera: Odontomerella Hendel, 1912 and Maerorichardia Hennig, 1937, both known only from the holotypes of their type species. Maerorichardia is the only genus of Richardiidae with mid and hind tibiae thicker than their respective femora, and the wing with the anal lobe distinctly developed. Odontomerella can be distinguished from the others richardiids by the postcranium reduced and little wider ventrally, the compound eye well developed, occupying most of the head, with the gena and postcranium very reduced, and the face short, with the oral margin distinctly concave. The limits of both genera are revised and better supported with the addition of new diagnostic characters. Odontomera flavipleura Hennig, 1938 is transferred to Odontomerella. The types of the species are revised and illustrated.